The Advanced Proposed Architecture of Eco-Currency: Technical Analysis of West Africa Single Currency Program - TWENEBOAH SENZU, Emmanuel (Journal of Advanced Studies in Finance; Vol 11 No 2 (2020): JASF Volume XI Issue 2(22) Winter 2020DO - 10.14505//jasf.v11.2(22).03, 2020)
The different target of the time period has been established over the past two decades in the institutionalization of a single currency union in West Africa. Depending on varied reasons the proposed programs have always failed before the set timelines in respect of ECOWAS monetary unification and single currency adoption. As a result, the paper explored and developed its argument based on the existing studies of structured economic shocks, significant to the failure of the single currency union, and its major causal factors. And with observed structured analysis propose catalytic activator method as a theoretical guide to attain the single currency union within three (3) years ahead, if the necessary requirement as the commitment level of members’ State is applied towards the single currency unification program. It then elaborates in the spirit of precision the process required to sustain the eco-currency program in other to elevate members State in an out-date of its domestic currencies struggling as a subservient economic bloc to the adoption of a new anticipated domineering currency in its own merit to shoulder with the global dominating hard currencies.